Stimulating fundamental movement skills through field games: An experimental study on elementary school students - Gustian, Uray; Samodra, Y Touvan Juni; Mardiyyaningsih, Asriah Nurdini; Ghasya, Dyoty Auliya Vilda; Mashud (Edu Sportivo: Indonesian Journal of Physical Education, 2023)
Basic movement skills are the skills needed to explore the body’s ability to move as a result of learning to respond to stimuli. However, the learning process is still focused on mastering the skills but does not include the cognitive abilities. The research aims to measure the success of implementing field games in stimulating elementary school students' fundamental movement skills. The experiment adopted the one-group pretest and posttest designs. It was conducted in three consecutive stages: pretest, treatment, and posttest. The study involved a sample of 126 students who were randomly taken from elementary schools in Pontianak. The data on fundamental movement skills were collected through the Test of Gross Motor Development-2 (TGMD-2) instrument, which was analyzed descriptively. The results of the study showed that there had been an increase in the average TGMD-2 score of students on the posttest when compared to the pretest. The t-test between pre- and post-test showed that the scores were significantly different, as suggested by the calculated t-value having a greater value than the t-table. This result indicates that the implementation of field games can stimulate fundamental movement skills. It is concluded that applying field games can improve students' fundamental movement skills and can be used as an alternative for teachers in carrying out motion learning at school.